Demetallisation of heavy metals from indian mackerel (R. kanagurta) fish - Nurasmat, Mohd Shukri; A. M., Shahrom; N. F., Muhamad Salleh; W. N., Wan Abdullah; N. Z., Md Muslim; N. S. A., Mohd Shohaimi; N. H., Abdullah; A. Z., Abd Halim (IOP Publishing Ltd., 2020)
Fish especially Indian Mackerel (R. kanagurta) provides protein, essential fatty acids and essential metals that are needed in the human diet, however high concentration of essential metals will cause adverse health effect towards human. Thus, the removal of heavy metals such as lead (Pb) and copper (Cu) from R. kanagurta (Indian mackerel) by using different types of natural waste adsorbents was implemented in this study. Initial concentration of heavy metals (Pb, Cu) in Indian mackerel (R. kanagurta) fish were above the permissible limit set by World Health Organization and Malaysia Food Regulation 1985. Thus, in this study, corncob and eggshell were applied as natural waste adsorbents to enhance the demetallisation process. The result showed only the corncob able to efficiently remove all the heavy metals in Indian Mackerel (R. kanagurta) up to 78.31% compared to the eggshell, which yielded about 71.34%. Besides, this study proved that using corncob; the Cd metal found to be wholly removed from (R. kanagurta) which met the permissible limit set by WHO and MFR.